Correlation between cervical lordosis and cervical disc herniation in young patients with neck pain. Issue 31 (August 2019) - Gao, Kun; Zhang, Jiliang; Lai, Jinquan; Liu, Weidong; Lyu, Hanqing; Wu, Yihong; Lin, Zhanpeng; Cao, Yafei
Abstract : Abstract: Abnormal cervical curvature and cervical disc herniation are closely related to neck pain and should be taken into account before any treatment. However, studies have rarely reported on the correlation between cervical lordosis and cervical disc herniation in patients with neck pain. Therefore, in this study, we collect young neck pain patients with abnormal cervical curvature to evaluate the relationship between cervical lordosis and cervical disc herniation. Three hundred patients below 40 years old with neck pain were enrolled. Patient sex, age, apical vertebra, segment of intervertebral disc protrusionl, sagittal diameter of spinal duramater, saggital diameter of spinal canal, height of disc space were recorded, and the cervical curvature, and degree of cervical spinal cord compression (G/F ratio) were calculated. The change of degree of disc herniation and degree of cervical spinal cord compression were analyzed in different cervical curvature groups. Further more, collected these patients who had improved cervical curvature over a period of time, to compare the changes of degree of disc herniation, G/F ratio, and height of disc space. The median age of patients with kyphosis was lower than those with lordosis and straight cervical spine. The degree of disc herniation was higher in the straight and kyphosis groups compared to the lordosis group. Cervical lordosis was inversely correlated with the degree of disc herniation and positively with G/F ratio. Cervical curvature was significantly affected by sex, age, and the degree of disc herniation. With the improvement of cervical lordotic curvature, the degree of disc herniation decreased and height of disc space increased. The degree of disc herniation and cervical spinal cord compression are inversely correlated to cervical lordosis in young neck pain patients, and the degree of disc herniation and height of disc space can recover with the recovery of cervical lordotic curvature. These findings may indicating a link between cervical curvature and degenerative changes which have important clinical implications.